Ongoing antiarrhythmic drug therapy type does not affect the rate of first-pass pulmonary vein isolation: data from a multicenter registry. (14th October 2021) - Gasimova, N; Kropotkin, E; Ivanitsky, E; Kolunin, G; Nechepurenko, A; Shavshin, D; Antolic, B; Kovalev, K; Mikhaylov, E; Lebedev, D
Abstract: Background: It is well-known that antiarrhythmic drugs (AAD) change the electrophysiological properties of the atrium mostly by increasing the atrial refractory period and wavelength for reentry. Frequently, atrial fibrillation (AF) catheter ablation is being performed with AAD interruption. However, the information on the impact of AAD on AF ablation performance is lacking, and AAD interruption is not desirable in highly symptomatic patients with persistent arrhythmia. Purpose: We sought to study potential differences in achieving first-pass pulmonary vein isolation (FPI) during AF ablation in patients receiving different classes of ongoing AADs. Methods: This was a prospective observational multicenter registry. All centers were invited to participate in the registry voluntarily. Data on demographic, clinical, and procedure characteristics were derived from a web-based system. All catheter ablation procedures were performed according to local practices. A total of 450 patients were enrolled, 408 of them underwent first-time AF ablation. Data on AAD characteristics were available in 350 patients (mean age 61±9 years, 195 (56%) males, 270 (77%) had paroxysmal AF). All patients were divided into three groups: ongoing I class AAD treatment (propafenone, ethacyzin, allapinin, n=76), ongoing II class AAD (beta-blockers, n=60), and ongoing III class AAD (amiodarone, sotalol, n=214). Results: Baseline clinical and procedural characteristics between AAD groups are summarized in Table. Patients in the I class AAD group were younger, likely had paroxysmal AF, and a smaller mean left atrial diameter. Procedures in the III class AAD group were performed with a higher median target ablation index on the posterior left atrial wall. But the percentage of first-pass isolation was distributed equally between groups (60%, 68%, 61%, p=0.56). The correlation matrix revealed no significant associations between FPI and clinical and procedural variables (r=0.02–0.09; p>0.05 for all). Conclusion(s): Our real-life multicenter data demonstrate no difference in FPI achievement between patients receiving different AADs. We suggest that highly symptomatic patients may continue pharmacological treatment during AF ablation without compromising acute ablation success. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Ministry of Science and Higher Education grant (Russian Federation President Grant)